Students' perceptions of autonomy in the context of their experiences in remote learning - Wioletta Kwiatkowska; Agata Ćwiek (Studia z Teorii Wychowania)
The aim of this article is to present the possibilities and limitations associated with the autonomy of remote learners. The experiences of students of science, humanities and social sciences were analyzed. Answers to the following questions were sought: 1) What is the autonomy of remote learners? 2) What was beneficial for autonomy and what were the negative experiences? 3) What is important for the proper development of autonomy in remote learning? The results of the study show the importance of mutual trust (in the relationship between the entities of the academic education process) in the context of the autonomy felt by students. The respondents also pointed out the need to respect their privacy, treating them subjectively and promoting autonomous attitudes. They emphasized the need to improve educational and organizational tools and strategies for remote education to enable self-management of one's own educational process. There is a need for greater care and support for learners' sense of autonomy.